Organoleptic and Nutrient Tests of Bareh Randang Formula with the Addition of Curd to Reduce Hypercholesterolemia - Lastrie Asrya (Majalah Kedokteran Andalas, 2024)
Objective: This study aims to determine the organoleptic test and nutritional content of the Bareh Randang formula with the addition of curd to reduce hypercholesterolemia. Method: This type of research is experimental by conducting direct experiments using a Completely Randomized Design (CRD) with four levels of curd addition, namely 0 gr, 15 gr, 25 gr and 35 gr per dough formula which is carried out in two repetitions. Organoleptic tests were carried out by 25 panelists. Data were analyzed using the Kruskal Wallis test and Mann Whitney advanced test. Laboratory tests carried out proximate nutrient content tests and BAL tests. Results: Based on organoleptic tests, the best formula was obtained with the addition of 25 grams of curd. The results of the Kruskal Wallis test showed that there was a significant difference of P<0.05 in color, taste and texture, while in aroma there was no significant difference of P>0.05. From testing the LAB content, it was found that the bareh randang product contained LAB 108 CFU/g which is useful as a probiotic food. Conclusion: When making bareh randang products, it is best to add 25 grams of curd.